Upaya Menghadapi Kejahatan Terhadap Sistem Keamanan Perbankan Indonesia Di Era Cyberspace - Sari, Clara Mega Kharisma; Zulfiani, Anita; Suharto, Suharto; Muhyidin, Muhyidin (Law, Development and Justice Review, 2024)
In this Cyberspace Era, the system of life in society, both Indonesian and world, has changed a lot, this can have a complete impact on people's lives, both in the form of positive and negative impacts. Along with the development of the cyber world, this is directly proportional to crime in the banking sector, these crimes are related to the banking security system. There are many crimes against the banking security system including carding crimes "credit card fraud", ATM or EDC "skimming", hacking, cracking, phishing "internet banking fraud", malware "virus/worm/trojan/bots", cybersquatting, pornography, gambling online, transnational crime “drug trafficking, mafia, terrorism, money laundering, human trafficking, underground economy”. From these various crimes, to prevent crimes against the banking security system, the government can carry out various efforts, including efforts related to banking security system policies and various efforts that can be made, such as various narratives and outreach to the public. Apart from the government, banks and the public must also implement principles related to banking system security. This research uses a normative juridical method, namely an approach based on the main legal material by examining theories, concepts and principles related to the banking security system. In order to achieve a good banking security system, cooperation between the government, the bank and the community is required.